INVENTARISASI JENIS-JENIS TUMBUHAN OBAT DI KECAMATAN ROTE TENGAH KABUPATEN ROTE NDAO - Nge, Sonya Titin; Ballo, Apriliana; Busu, Yurika (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The people of Central Rote sub-district, namely in Lidabesi village, Lidamanu village, and Limakoli village, still use plants as a traditional medicine because they are easily accessible in terms of price and availability and do not require expensive costs to obtain so plants as traditional medicine are a priority alternative treatment. This research aims to find out what types and uses of plants are used as medicinal plants in Rote Tengah District, Rote Ndao Regency. This research was conducted in October-December 2023. The method used in this research was the exploration and interview method, while the data collection technique was carried out by exploratory interviews. Work procedures include a preparation stage consisting of observation and determining the location and implementation stages. The data analysis technique uses qualitative descriptive analysis which is used to describe the types of medicinal plants that have been identified by describing them in the form of tables and pictures from the results of respondent interviews. Based on the research results, 33 types of plants with medicinal properties were obtained which were used by the community. Diseases that can be cured include fever, cough, colds, stomach ulcers, white blood, stomach ache, high blood pressure, diarrhea, urinary stones, sugar, shortness of breath, cancer, headaches, asthma, urinary tract infections, heart disease, new wounds, broken bones, chicken pox, toothache, body itching, body odor, yellow eyes, boils, bleeding and difficulty giving birth. The plant organs used are roots, stems, bark, leaves, shoots, fruit, seeds, and tubers. Processing is done by boiling, soaking, chewing, burning, pounding, sticking, and using straight away.